Consumer Interest Tracking and Data Acquisition System (International Journal of Engineering and Computer Science, 2018)
In the modern world, growth is a factor every company seeks for, And Growth isdetermined by the amount of revenue they generate, the number of consumers they satisfy etc. Forproduct based companies, achieving Greater number of sales is their key objective. And it achieved byunderstanding customers’ requirements, employing various marketing strategy, carrying out relevantanalysis, advertisement etc., and all of these factors pose a great challenge for every enterprise andcompanies around the world, but foremost understanding the customers interest is the greatest challengeof all. Every time we step into a mall or Exhibition, It is the natural tendency of a person to spend moretime with the object that meets their interest, but till now we have never kept the track of the interactionbetween the consumers and product with respect to time. In our project, with the help of wirelesscommunication & ubiquitous sensors such as RFID and proper GUI, we are developing a consumerinterest tracking device which is capable of gathering valuable information regarding time spent by anindividual at various stores, Products in an exhibition or shopping mall. Based on the informationcollected we determine the interest of consumer, which in turn help the company to manufacture betterproducts, take smarter decisions and ensure a safer future for the enterprise. The information gathered ismade available for real-time monitoring, or can be stored for future analysis